Knowledge management system as enabler in knowledge management practices in virtual communities - Assegaff, Setiawan (2013)
Knowledge Management System was recognized as one of the key enablers in a Knowledge Management initiative. This is because KMS have been prove bring value for Knowledge Management initiatives such as eliminate distance and time barriers. Furthermore KMS also made KM more effective for the organization. As general KMS have two main functions, first managing people interaction and managing information/knowledge. Because knowledge creates from the interaction of the people, than KMS has a vital function in knowledge creation with managing people interaction. In KM on an organization, they conduct interaction by developing some activities such as: Communities of Practices, Communities of Interest, Peer Assist and Share Learning as a method to create and leverage the knowledge. The activities could be conducted manually or virtually. In support that activities done in virtual, using IT could bring potential value. In this study we would like to propose the framework for organizations on how to implement KMS as a powerful enabler for KM in virtual communities.